HUBUNGAN STIMULASI ORANG TUA DENGAN PERKEMBANGAN BICARA DAN BAHASA PADA ANAK TODDLER DI POSYANDU DADAP KELURAHAN BENCONGAN INDAH KABUPATEN TANGERANG TAHUN 2021 - Ayu Lestania; Siti Haeriyah (Nusantara Hasana Berdikari, 2022)
Optimizing child development will never be separated from how parents provide stimulation to their children. The slow development of children in language and speaking tends to be higher than other developing countries. The purpose of this study was to determine whether there is a relationship between Parental Stimulation with Speech and Language Development in Toddler Age Children at Posyandu Indah Kelapa Dua Tangerang in 2021. The research method used is: This type of research uses a quantitative research design with a Cross Sectional approach. The sampling technique used in this research is saturated sampling technique or total sampling with a total sample of 44 respondents. The results showed that based on the results of the study, it was found that there was a relationship between parental stimulation and children's speech and language development using the Chi Square test, the P Value = 0.019, meaning (p < 0.05) there was a relationship and the OR value was 0.175. Conclusions and Suggestions: Based on the results of this study, parents are expected to always stimulate children optimally so that their development can be in accordance with the child's age.